Planning and design of rural villages :a case study of Bidayuh villages in Bau district, Sarawak - Wee, Irene Siew Liang (Universiti Malaysia Sarawak (UNIMAS), 2002)
Rural develoment is an important national development agenda. In the decades following independence many economic and infrastructural efforts have been channelled to improve rural areas and bring them into the mainstream of decelopment. Nevertheless, the physical aspect of village development has never been given due attention. Sarawak in particular does not have appropriate planning controls that can be applied specifically to traditional rural villages akthough a very important guideline known as the Development Control Standard has been in used since 1968.